Electrodes, batteries and battery packs
The electrode design with specific particle size distribution and uneven distribution of lithium-containing metal oxides in the mixture layer addresses capacity reduction and cycle performance issues by enhancing packing density and suppressing gas release, resulting in high-capacity batteries with improved charge/discharge performance.
Patent Information
- Application Number
- JP2022550384
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-09-18
- Filing Date
- 2021-07-20
- Publication Date
- 2024-12-16
- Estimated Expiration
- 2041-07-20
AI Technical Summary
Existing electrodes and batteries face issues with capacity reduction due to gas generation and sliding of the active material during high-temperature storage, leading to decreased charge/discharge cycle performance, particularly at high temperatures.
The electrode design includes a mixture layer with a specific distribution of first and second lithium-containing metal oxide particles, where the first particles have an average size of 8-25 μm and second particles have an average size of 1-6 μm, with an abundance ratio of 60-90% and uneven distribution within a defined range, enhancing packing density and suppressing gas release.
This configuration results in electrodes with high capacity and improved charge/discharge cycle performance, particularly at high temperatures, by reducing gas generation and mixture layer sliding.
Smart Images

Figure 0007600254000003 
Figure 0007600254000004 
Figure 0007600254000005
Abstract
Description
[Technical field]
[0001] SUMMARY OF THE DISCLOSURE Embodiments of the present invention relate to electrodes, batteries, and battery packs. [Background technology]
[0002] It has been reported that the use of active materials with different particle sizes can improve the electrode density and provide nonaqueous electrolyte batteries with excellent input / output characteristics. However, no attention has been paid to the distribution of large and small particle sizes in the thickness direction of the electrode. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Publication No. 2019-067541 [Patent Document 2] Japanese Patent Publication No. 2009-117241 [Patent Document 3] Japanese Patent Application Publication No. 2016-55254 [Patent Document 4] Japan Special Publication No. 2013-504168 [Patent Document 5] Japan Special Publication No. 2015-528181 Summary of the Invention [Problem to be solved by the invention]
[0004] The object is to provide an electrode, a battery, and a battery pack that have high capacity and excellent life characteristics. [Means for solving the problem]
[0005] According to the embodiment, an electrode is provided that includes a current collector and a mixture layer formed on at least one surface of the current collector and containing an active material. The active material includes first particles of a lithium-containing metal oxide and an average particle size D of the first particles. 1 Average particle size D smaller than 2and a second particle of a lithium-containing metal oxide having the formula (1) below. The existence ratio of the first particle and the second particle represented by the formula (1) below is 60% or more and 90% or less.
[0006] {A1 / (A1+A2)}×100 (1) When the distance from the first surface of the mixture layer that contacts the current collector to the second surface that does not contact the current collector is T, A1 is the total area of the first particles on the surface of the mixture layer that has the length of distance T, and A2 is the total area of the second particles on the surface of the mixture layer that has the length of distance T.
[0007] Distance 2D from the first surface to the second surface 1 / T, the first particles are unevenly distributed in a range such that the ratio satisfies the following formula (2).
[0008] (A3 / A1)≧2D 1 / T×1.05 (2) Here, A3 is the distance 2D from the first surface to the second surface on the surface of the mixture layer having a length of the distance T. 1 / T is the sum of the areas of the first particles present in the range. The particle size of the first particle is within a range of 8 μm or more and 25 μm or less. The average value is the average particle size D 1 It is. The particle size of the second particle is within the range of 1 μm to 6 μm and is smaller than the particle size of the first particle. The average value is the average particle size D 2 is .
[0009] According to another embodiment, a battery is provided that includes a positive electrode formed from an electrode according to the above embodiment and a negative electrode.
[0010] According to another embodiment, a battery pack is provided that includes a battery according to the above embodiment. [Brief description of the drawings]
[0011] [Figure 1] FIG. 2 is a schematic diagram showing an example of a cross section of a mixture layer of an electrode according to an embodiment. [Diagram 2]FIG. 2 is a plan view showing an outline of a sample obtained from the electrode of the embodiment. [Diagram 3] FIG. 4 is a plan view showing an example of an electrode group. [Figure 4] FIG. 11 is a plan view showing another example of an electrode group. [Diagram 5] FIG. 2 is a partially cutaway perspective view showing an example of a battery according to an embodiment. [Figure 6] FIG. 6 is an enlarged cross-sectional view of part A of the battery shown in FIG. 5 . [Figure 7] FIG. 4 is a partially cutaway perspective view showing another example of a battery according to an embodiment. [Figure 8] FIG. 13 is a partially cutaway perspective view showing still another example of a battery according to an embodiment. [Figure 9] FIG. 9 is an enlarged cross-sectional view of part B of the battery shown in FIG. 8 . [Figure 10] FIG. 2 is an exploded perspective view showing an example of a battery pack according to an embodiment. [Figure 11] FIG. 11 is a block diagram showing an example of an electric circuit of the battery pack shown in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] (First embodiment) Hereinafter, the embodiments will be described with reference to the drawings. In the following description, components that perform the same or similar functions are given the same reference numerals throughout the drawings, and duplicated descriptions will be omitted. Note that each figure is a schematic diagram for explaining the embodiment and facilitating understanding thereof, and the shapes, dimensions, ratios, etc. may differ from the actual device, but these can be appropriately modified in design by taking into consideration the following description and known techniques. Patent Document 1 discloses that by setting the average particle size of the granules contained in the positive electrode mixture layer to 0.9 μm or more and 2 μm or less, and setting the particle size of 90% or more of the granules to 0.25 μm or more and 3.5 μm or less, it is possible to reduce the interfacial resistance between the current collector and the positive electrode mixture layer and improve the lithium ion conduction rate within the granules even if the pressure of the electrode is increased. Patent Document 2 discloses that by filling a lithium nickel manganese cobalt-based composite oxide powder having voids on the surface and inside of the secondary particles with fine particles smaller than the void size, it is possible to obtain a positive electrode active material powder with improved output characteristics by further using conductive fine particles as the void-filling fine particles. However, all of the technologies to date have problems with life performance.
[0013] The present inventors have discovered that when the ratio of small particle active material inside the electrode mixture layer is high, the amount of gas generated increases, and the active material slides out from inside the electrode mixture layer during high temperature storage, leading to a decrease in capacity. They have found that an electrode having the following configuration suppresses the amount of gas generated at high temperatures and improves life performance.
[0014] That is, the electrode according to the embodiment is an electrode including a current collector and a mixture layer formed on at least one surface of the current collector and including an active material, the active material being first particles of a lithium-containing metal oxide and an average particle diameter D 1 Average particle size D smaller than 2 and a second particle of a lithium-containing metal oxide having the formula (1) below. The existence ratio of the first particle and the second particle represented by the formula (1) below is 60% or more and 90% or less.
[0015] {A1 / (A1+A2)}×100 (1) When the distance from the first surface of the mixture layer that contacts the current collector to the second surface that does not contact the current collector is T, A1 is the total area of the first particles on the surface of the mixture layer having the length of the distance T (hereinafter referred to as the measurement surface), and A2 is the total area of the second particles on the measurement surface.
[0016] Also, the distance from the first surface to the second surface is 2D1 / T range (hereafter, 2D 1 / T region), the first particles are unevenly distributed at a ratio that satisfies the following formula (2).
[0017] (A3 / A1)≧2D 1 / T×1.05 (2) where A3 is the 2D 1 / T is the sum of the areas of the first particles present in the region.
[0018] First, the reason why the abundance ratio represented by formula (1) is set in the range of 60% or more and 90% or less will be explained. If the abundance ratio is set to less than 60%, the abundance ratio of the second particles becomes relatively high, and the surface area of the active material becomes large. As a result, the side reaction between the active material and the electrolyte becomes large, and the amount of gas generated increases. On the other hand, if the abundance ratio exceeds 90%, the particle diameter of the active material becomes uniform, and the packing density of the active material decreases. For the above reasons, the abundance ratio is preferably in the above range. A more preferable range of the abundance ratio is 70% or more and 85% or less.
[0019] Next, formula (2) will be described. Fig. 1 is a schematic diagram of an example of a cross section of an electrode of an embodiment cut in the lamination direction. The electrode E is, for example, a positive electrode, and includes a layered positive electrode current collector C and a positive electrode mixture layer M formed on each of both sides of the positive electrode current collector C. The positive electrode mixture layer M includes first particles P of a lithium-containing metal oxide and an average particle size D of the first particles. 1 Average particle size D smaller than 2 and second particles Q of a lithium-containing metal oxide having a thickness of 100 nm. The surface of the positive electrode mixture layer M that is in contact with the positive electrode current collector C is designated as a first surface S1, and the surface that is not in contact with the positive electrode current collector C is designated as a second surface S2. The distance from the second surface S2 to the first surface S1 is designated as T. In the above-mentioned measurement surface, a distance 2D in the direction from the first surface S1 to the second surface S2 is designated as T. 1 / T (2D 1 / T region) at a ratio that satisfies equation (2). 1The ratio of the area A3 of the first particles P present in the / T region is expressed as (A3 / A1). When the existence ratio expressed by formula (1) is 60% or more and 90% or less, the ratio (A3 / A1) is 2D 1 If the ratio is less than the value expressed by / T × 1.05, the gas escape from the mixture layer is reduced, causing the mixture layer to slide off during charge-discharge cycles. As a result, the capacity loss due to gas generation at high temperatures increases, and the charge-discharge cycle performance, especially the charge-discharge cycle performance at high temperatures, decreases. When the ratio expressed by formula (1) is set to 60% or more and 90% or less, and the ratio of (A3 / A1) is set to 2D 1 By making the value represented by / T×1.05 or more, the gas escape from the mixture layer is improved, so that the mixture layer can be prevented from slipping off during charge-discharge cycles. As a result, the capacity reduction due to gas generation at high temperatures can be suppressed, so that the charge-discharge cycle performance, especially the charge-discharge cycle performance at high temperatures, can be improved. In addition, the packing density of the active material can be increased, so that a high capacity can be obtained. Therefore, an electrode capable of realizing a battery with high capacity and excellent charge-discharge cycle performance can be provided.
[0020] D 1 , D 2 The measurement method is as follows.
[0021] The distance T, i.e., the thickness of the mixture layer, is measured as follows. It can be obtained by observing a cross section of the electrode cut along its lamination direction, for example, the cross section shown in FIG. 1, with a scanning electron microscope (SEM). As shown in FIG. 2, a 5 cm section of the electrode E is selected in an arbitrary direction (hereinafter, X direction), and divided into 5 in a direction perpendicular to the X direction (hereinafter, Y direction) to obtain 5 samples. Sample Z located at the center in the X direction among the obtained 5 samples is used as the measurement sample. The width of sample Z in the Y direction is divided into 2 to obtain two cross sections. An example of a cross section is shown in FIG. 1. An arbitrary cross section among the two obtained cross sections is observed with an SEM, and the distance between the contact point of the mixture layer and the current collector and the surface of the mixture layer that is not in contact with the current collector is measured at 4 positions (for example, shown by the dashed line in FIG. 1) that divide the range observed at a magnification of 1000 times into 5 equal parts, and the average value of the measured values obtained at the 4 points is taken as the thickness T of the mixture layer.
[0022] D 1 , D 2 The measurement method of is as follows. The same cross section used in the measurement of T is observed with SEM-EDX at a magnification of 1000 times and an acceleration voltage of 5 kV to 15 kV, and the longest dimension D of the particle is measured. Particles with a diameter of D of 8 μm or more are regarded as the first particle, and the average diameter of the first particle is regarded as D. 1 Particles with a diameter of less than 8 μm are defined as second particles, and the average diameter of these particles is defined as D 2 The composition of each particle can be confirmed by elemental mapping using EDX.
[0023] A1 and A2 can be calculated as follows. 1 , D 2 In SEM-EDX observation performed under the same conditions as in the measurement of , the sum of the areas of particles (first particles) having a diameter D of 8 μm or more is defined as A1, and the sum of the areas of particles (second particles) having a diameter D of less than 8 μm is defined as A2.
[0024] A3 is D above 1 , D 2 In SEM-EDX observations performed under the same conditions as in the measurements, 1 / T region, D is the total area of particles (first particles) with a particle size of 8 μm or more. However, if a mixture layer is formed on both sides of the current collector, A3 is obtained for each surface having a length equal to the distance T of the mixture layer formed on one side of the current collector, and for each surface having a length equal to the distance T of the mixture layer formed on the other side of the current collector. The average value of the obtained A3 is used.
[0025] The electrodes of the embodiment will be further described below.
[0026] The electrode includes a current collector and a mixture layer formed on at least one surface of the current collector. The mixture layer includes an active material, and may optionally include a binder and a conductive agent.
[0027] The electrode can be applied to a positive electrode or a negative electrode. An example of application to a positive electrode will be described below.
[0028] The positive electrode active material includes first particles of a lithium-containing metal oxide and second particles of a lithium-containing metal oxide having an average particle diameter D smaller than the average particle diameter D of the first particles. Examples of the lithium-containing metal oxide include lithium-containing nickel cobalt manganese composite oxides, lithium-containing nickel manganese composite oxides (e.g., Li 1 Co 2 Mn x Ni 1-y-z O y Ni z O 2 , 0 < x ≦ 1, 0 < y ≦ 1, 0 < z ≦ 1, 0 ≦ 1 - y - z ≦ 1), lithium-containing manganese composite oxides (e.g., Li x Mn 2 O 4 or Li x MnO 2 , 0 < x ≦ 1), lithium-containing cobalt composite oxides (Li x CoO 2 , 0 < x ≦ 1), lithium-containing manganese cobalt composite oxides (LixMn 2-y Co y O 4 , 0 < x ≦ 1, 0 < y < 2), lithium iron composite oxides (e.g., Li x FePO 4 , Li x Fe 1-y Mn y PO 4 , 0 < x ≦ 1, 0 ≦ y < 1), etc. The type of the lithium-containing metal oxide can be one type or two or more types. The composition of the first particles and the composition of the second particles may be the same or different. Also, positive electrode active material particles other than the first particles and the second particles may be included. In this case, it is desirable that the ratio of the total weight of the first particles and the second particles in the positive electrode active material be 80% by weight or more and 90% by weight or less.
[0029] Among the lithium-containing metal oxides, lithium-containing nickel cobalt manganese composite oxides are preferred. The lithium-containing nickel cobalt manganese composite oxide is, for example, Li a Ni (1-x-y) Co x Mn y O 2It is represented by (0.9 ≦ a ≦ 1.2, 0 < x ≦ 0.5, 0 < y ≦ 0.5, x ≧ y, 0.6 ≦ 1 - x - y ≦ 0.9). The positive electrode active material preferably contains first particles of a lithium-containing nickel cobalt manganese composite oxide and second particles of a lithium-containing nickel cobalt manganese composite oxide. More preferably, the positive electrode active material contains first particles of a lithium-containing nickel cobalt manganese composite oxide, second particles of a lithium-containing nickel cobalt manganese composite oxide, and particles of a lithium-containing cobalt composite oxide. Further preferred examples of the lithium-containing metal oxide include a lithium-containing nickel manganese composite oxide and a lithium-containing manganese composite oxide. By using a lithium-containing nickel manganese composite oxide, a lithium-containing manganese composite oxide, or a mixture thereof as the lithium-containing metal oxide, the life performance of the electrode and the battery can be improved. More preferably, the positive electrode active material contains a lithium-containing metal oxide and a lithium-containing cobalt composite oxide. Even more preferably, examples of the positive electrode active material include those containing at least one lithium-containing metal oxide selected from the group consisting of a lithium-containing nickel cobalt manganese composite oxide, a lithium-containing nickel manganese composite oxide, and a lithium-containing manganese composite oxide. Thereby, the life performance of the electrode and the battery can be improved. This positive electrode active material preferably further contains a lithium-containing cobalt composite oxide in addition to the above lithium-containing metal oxide.
[0030] The positive electrode active material may be primary particles or secondary particles formed by aggregation of primary particles.
[0031] It is preferable that the particle size of the first particles is in the range of 8 μm or more and 25 μm or less, the particle size of the second particles is in the range of 0.5 μm or more and 7 μm or less, and the particle size of the second particles is smaller than that of the first particles. Thereby, the effect of suppressing the dropout of the active material from the positive electrode due to gas generation can be enhanced. More preferably, the particle size of the second particles is in the range of 1 μm or more and 6 μm or less. The positive electrode may contain a conductive agent having a secondary particle shape as the conductive agent. This positive electrode preferably satisfies the following formula (3). T2S>2×T1S (3) Here, T1S is the total area (μm2) of the conductive agent contained in the region from the first surface to the second surface up to a distance T / 2 on the surface (measurement surface) of the mixture layer having a length of T. 2 ) T2S is the total area (μm2) of the conductive material contained in the region from the second surface to the first surface at a distance of T / 2 on the aforementioned measurement surface. 2 ).
[0032] T1S and T2S are measured as follows: 1 , D 2 In SEM-EDX observation performed under the same conditions as in the measurement of (1), for example, as shown in FIG. 1, the total area (μm 2 ) is defined as T1S. The total area (μm 2 However, if a mixture layer is formed on both sides of the current collector, find T1S and T2S for each side of the surface having the length T of the mixture layer formed on one side of the current collector, and for each side of the surface having the length T of the mixture layer formed on the other side of the current collector, and then compare T1S and T2S. By satisfying the above formula (3), it is possible to suppress the occurrence of bias in the current distribution in the second surface, which is not in contact with the current collector and is separated from the current collector, and in the vicinity thereof, and therefore it is possible to suppress the deterioration of the positive electrode active material in the vicinity of the second surface of the mixture layer, thereby improving the life performance of the electrode of the embodiment and thereby improving the life performance of the battery.
[0033] Any binder that is normally used in non-aqueous electrolyte batteries can be used. For example, electrochemically stable polyvinylidene fluoride (PVdF), polytetrafluoroethylene, etc. can be used. The type of binder can be one or more types.
[0034] The conductive agent can be any material having suitable electrical conductivity. For example, carbon black such as acetylene black, or carbon such as graphite can be used. The conductive agent can be of one type or two or more types. An example of a conductive agent in the form of secondary particles includes acetylene black.
[0035] The positive electrode current collector can be a conductive thin film having a positive electrode mixture layer on one or both sides. The positive electrode current collector can be a non-perforated metal foil, a punched metal having a large number of holes, a metal mesh formed from thin metal wires, or the like. The positive electrode current collector can be, for example, a metal foil or an alloy foil. Examples of the metal foil include aluminum foil, copper foil, and nickel foil. Examples of the alloy include aluminum alloy, copper alloy, and nickel alloy.
[0036] The material of the positive electrode current collector is not particularly limited as long as it does not dissolve in the battery usage environment, and for example, metals such as Al and Ti, and alloys containing the above metals as the main component and one or more elements selected from the group consisting of Zn, Mn, Fe, Cu, and Si can be used. In particular, aluminum alloy foils containing Al as the main component are preferably thin films that are flexible and have excellent formability. The thickness of the positive electrode current collector is typically preferably 5 μm or more and 20 μm or less.
[0037] The mixing weight ratio of the positive electrode active material, the conductive agent, and the binder is preferably 80% or more and 96% or less of the positive electrode active material, 3% or more and 15% or less of the conductive agent, and 0.5% or more and 5% or less of the binder. By making the amount of the conductive agent 3% or more, the current collection performance of the positive electrode mixture layer can be improved. Also, by making the amount of the binder 0.5% or more, the binding property between the positive electrode mixture layer and the negative electrode current collector can be improved, and excellent cycle characteristics can be expected. On the other hand, it is preferable to make the total amount of the conductive agent and the binder 20% by weight or less in order to achieve high capacity. The positive electrode density (positive electrode packing density) is preferably 2.8 g / cc or more and 3.6 g / cc or less from the viewpoints of increasing capacity, input / output characteristics, and gas escape from the mixture layer.
[0038] A portion of the positive electrode current collector on which the positive electrode mixture layer is not formed can serve as a positive electrode current collecting tab.
[0039] The positive electrode is obtained, for example, by the following method. A positive electrode active material including first and second particles and a conductive agent are dry-mixed. A first solvent is added to the obtained mixed powder and binder, and the mixture is kneaded (solid kneaded) to prepare a first slurry. Then, a second solvent is added to the first slurry and stirred to prepare a second slurry. The second slurry is applied to at least one surface of a current collector, dried, and pressed to obtain a positive electrode. Cutting is performed as necessary. According to this method for producing a positive electrode, the solid content ratio of the second slurry is within a range suitable for application to a current collector, and the solid content ratio of the first slurry is higher than that of the second slurry. Therefore, the first slurry has a higher viscosity than the second slurry, and it becomes easier to disintegrate aggregates (for example, aggregates of a conductive agent in the form of secondary particles) contained in the first slurry by kneading (solid kneading). As a result, the active material and the conductive agent can be uniformly dispersed in the first slurry. Then, the second solvent is added to the first slurry and stirred to prepare a second slurry in which the active material and conductive agent are uniformly dispersed. When the second slurry is applied to at least one surface of a current collector, the active material particles with a large particle size settle to the current collector side due to their large specific gravity, and the conductive agent, which has a smaller specific gravity than the active material particles, is dispersed on the surface of the layer formed by application. By drying and pressing this, a positive electrode according to the embodiment, particularly a positive electrode that also satisfies formula (3), is obtained. In addition, since the active material and conductive agent are uniformly dispersed in the second slurry, when the layered product obtained is pressed after drying the second slurry applied to the current collector, the packing density can be easily increased, and a high-density electrode can be obtained.
[0040] The first solvent and the second solvent may be the same or different from each other. Examples of the first solvent and the second solvent include organic solvents such as N-methylpyrrolidone (NMP) and water.
[0041] <Measurement of active material composition> The composition of the active material contained in the electrode can be determined as follows.
[0042] The active material-containing layer is peeled off from the electrode as a measurement sample using, for example, a spatula to obtain a powdered sample.
[0043] The crystal structure of the active material is identified by powder X-ray diffraction (XRD) measurement of the powdered sample. The measurement is performed using CuKα radiation as the radiation source in the measurement range of 2θ between 10° and 90°. This measurement makes it possible to obtain the X-ray diffraction pattern of the compound contained in the selected particles.
[0044] As an apparatus for powder X-ray diffraction measurement, for example, SmartLab manufactured by Rigaku Co., Ltd. is used. The measurement conditions are as follows: X-ray source: Cu target Output: 45kV, 200mA Soller slit: 5° for both incidence and reception Step width: 0.02 deg Scan speed: 20deg / min Semiconductor detector: D / teX Ultra 250 Sample plate holder: Flat glass sample plate holder (thickness 0.5 mm) Measurement range: 10°≦2θ≦90°.
[0045] When using other equipment, perform the measurement using standard Si powder for powder X-ray diffraction so as to obtain measurement results equivalent to those described above, and adjust the measurement conditions so that the peak intensity and peak top position match those of the above equipment.
[0046] Next, the sample containing the active material is observed using a scanning electron microscope (SEM). It is desirable to observe the sample in an inert atmosphere such as argon or nitrogen without exposing the sample to the air during SEM observation.
[0047] For example, several particles having the form of primary particles or secondary particles that can be confirmed within the field of view in a 3000x SEM observation image are selected. In this case, the selected particles are selected so that the particle size distribution is as wide as possible. The types and composition of the constituent elements of the active material are identified by EDX analysis of the observed active material particles. This makes it possible to identify the types and amounts of elements other than Li contained in each selected particle. The same operation is performed on each of the multiple active material particles to determine the mixed state of the active material particles.
[0048] Next, the powder sample taken from the active material-containing layer as described above is washed with acetone and dried. The obtained powder is dissolved in hydrochloric acid, the conductive agent is removed by filtration, and then the solution is diluted with ion-exchanged water to prepare a measurement sample. The metal ratio in the measurement sample is calculated by inductively coupled plasma atomic emission spectroscopy (ICP-AES) analysis.
[0049] When there are multiple types of active materials, the weight ratio is estimated from the content ratio of elements specific to each active material. The ratio of the weight of the specific elements to the active material is determined from the composition of the constituent elements obtained by EDX analysis. For example, the measurement sample obtained from the active material-containing layer may contain a lithium-containing nickel-cobalt-manganese composite oxide as the first active material and a lithium-containing cobalt composite oxide as the second active material. In this case, the chemical formula and formula weight of each of the first and second active materials are calculated from the obtained metal ratio, and the weight ratio of the first and second active materials contained in the sampled active material-containing layer of a predetermined weight is obtained.
[0050] According to the electrode of the first embodiment described above, the active material is composed of the first particles of a lithium-containing metal oxide and the first particles having an average particle diameter D 1 Average particle size D smaller than 2 The first particles are present in a greater proportion than the second particles. In addition, when the distance from the first surface of the mixture layer that contacts the current collector to the second surface that does not contact the current collector is T, the distance from the first surface to the second surface is 2D 1 / T. With such an electrode, a battery having a high capacity and excellent charge / discharge cycle performance can be realized. Second Embodiment The second embodiment relates to a battery. The battery of the embodiment includes a positive electrode made of the electrode of the first embodiment, a negative electrode, and a non-aqueous electrolyte. The battery of the embodiment may further include a separator. The battery of the embodiment may also include an electrode group including a positive electrode, a negative electrode, and a separator. In this case, the non-aqueous electrolyte may be held in the electrode group.
[0051] The negative electrode, the non-aqueous electrolyte, and the separator will now be described. (Negative electrode) The negative electrode includes a negative electrode mixture layer containing a negative electrode active material, a conductive agent, and a binder, and a negative electrode current collector. A form in which the negative electrode mixture layer is present on one side or both sides of the negative electrode current collector is preferred, and a form in which the negative electrode mixture layer is present on both sides of the negative electrode current collector is more preferred. The negative electrode mixture layer is a layer in which the negative electrode active material, the conductive agent, and the binder are dispersed, and is provided on the negative electrode current collector.
[0052] Examples of the negative electrode active material include metal composite oxides, carbonaceous materials, metal compounds, etc. The type of the negative electrode active material may be one or more.
[0053] An example of a metal composite oxide is Li 4+x Ti 5 O 12 (x varies in the range of -1≦x≦3 depending on the charge / discharge reaction) 2+x Ti 3 O 7 (x varies in the range of -1≦x≦3 depending on the charge / discharge reaction), and metal composite oxides containing Ti and at least one element selected from the group consisting of P, V, Sn, Cu, Ni, and Fe. Examples of metal composite oxides containing Ti and at least one element selected from the group consisting of P, V, Sn, Cu, Ni, and Fe include TiO 2 -P 2 O 5 , TiO 2 -V2 O 5 、 TiO 2 -P 2 O 5 -SnO 2 、 TiO 2 -P 2 O 5 -MO (M is at least one element selected from the group consisting of Cu, Ni, and Fe) can be mentioned. In addition, niobium titanate composite oxides such as TiNb 2 O 7 and Ti 2 Nb 10 O 19 etc. can be mentioned. These metal composite oxides change into lithium titanium composite oxides when lithium is inserted by charging.
[0054] Examples of the carbonaceous material include natural graphite, artificial graphite, coke, vapor-grown carbon fiber, mesophase pitch-based carbon fiber, spherical carbon, and resin-fired carbon. More preferable carbonaceous materials include vapor-grown carbon fiber, mesophase pitch-based carbon fiber, and spherical carbon. The carbonaceous material preferably has an interplanar spacing d 002 of the (002) plane by X-ray diffraction of 0.34 nm or less.
[0055] As the metal compound, metal sulfide and metal nitride can be used. As the metal sulfide, for example, titanium sulfide such as TiS 2 , molybdenum sulfide such as MoS 2 , and iron sulfide such as FeS, FeS 2 , LixFeS 2 can be used. As the metal nitride, for example, lithium cobalt nitride (e.g., Li s Co t N, 0 < s < 4, 0 < t < 0.5) can be used.
[0056] Any conductive agent can be used as long as it is a material having appropriate conductivity. For example, carbon black such as acetylene black and carbon such as graphite can be used. The type of the conductive agent can be one type or two or more types.
[0057] The binder may be any one that is commonly used in non-aqueous electrolyte batteries. It is preferable to use electrochemically stable materials such as polyvinylidene fluoride (PVdF), polytetrafluoroethylene, carboxymethyl cellulose, styrene butadiene rubber, and mixtures thereof. The binder may be one or more types.
[0058] The negative electrode current collector is a conductive thin film having a negative electrode mixture layer provided on one or both sides thereof. The negative electrode current collector may be made of the same material as the positive electrode current collector.
[0059] The negative electrode is prepared, for example, by suspending the negative electrode active material, the conductive agent, and the binder in a suitable solvent, applying the prepared slurry to the negative electrode current collector, drying, and rolling. The negative electrode is a negative electrode current collector tab in the portion where the negative electrode mixture layer is not formed on the surface of the negative electrode current collector. The weight ratio of the negative electrode active material, the conductive agent, and the binder is preferably set so that the negative electrode active material is 80% or more and 96% or less, the conductive agent is 2% or more and 18% or less, and the binder is 1% or more and 5% or less. By setting the amount of the conductive agent to 2% or more, the current collection performance of the negative electrode mixture layer can be improved. In addition, by setting the amount of the binder to 1% or more, the binding property between the negative electrode mixture layer and the negative electrode current collector can be increased, and excellent cycle characteristics can be expected. On the other hand, it is preferable to set the total amount of the conductive agent and the binder to 20% or less in order to achieve high capacity. The negative electrode density (negative electrode packing density) is desirably 2.0 g / cc or more and 2.8 g / cc or less from the viewpoints of increasing capacity, input / output characteristics, and gas escape from the mixture layer. When the negative electrode satisfies at least one of these physical properties, the nonaqueous electrolyte battery of the embodiment suppresses side reactions with the electrolyte and enhances gas escape from the mixture layer when gas is generated, thereby improving the life characteristics. (Non-aqueous electrolyte) The non-aqueous electrolyte may be, for example, a non-aqueous electrolyte solution, a gel electrolyte, or a solid electrolyte. The non-aqueous electrolyte solution is a solution containing an electrolyte salt and a non-aqueous solvent. The electrolyte salt may be, for example, LiPF 6 , LiBF 4 , Li(CF 3 SO2 ) 2 N (lithium bistrifluoromethanesulfonylamide; commonly known as LiTFSI), LiCF 3 SO 3 (commonly known as LiTFS), Li(C 2 F 5 SO 2 ) 2 N (lithium bispentafluoroethanesulfonylamide; commonly known as LiBETI), LiClO 4 , LiAsF 6 , LiSbF 6 , lithium bis(oxalato)borate {LiB(C 2 O 4 ) 2 Lithium difluoro(trifluoro-2-oxido-2-trifluoro-methylpropionato(2-)-0,0)borate {LiBF 2 OCOOC(CF 3 ) 2 , commonly known as; LiBF 2 (HHIB)}. These electrolyte salts may be used alone or in combination of two or more.
[0060] The electrolyte salt concentration is preferably in the range of 0.5 mol / L to 3 mol / L, and more preferably in the range of 1 mol / L to 2 mol / L. By specifying the electrolyte concentration in this way, it is possible to further improve performance when a high load current is applied while suppressing the effect of an increase in viscosity due to an increase in the electrolyte salt concentration.
[0061] The non-aqueous solvent is not particularly limited, but may be, for example, a cyclic carbonate such as propylene carbonate (PC) or ethylene carbonate (EC), a chain carbonate such as diethyl carbonate (DEC), dimethyl carbonate (DMC), methyl ethyl carbonate (MEC), or dipropyl carbonate (DPC), 1,2-dimethoxyethane (DME), γ-butyrolactone (GBL), tetrahydrofuran (THF), 2-methyltetrahydrofuran (2-MeHF), 1,3-dioxolane, sulfolane, or acetonitrile (AN). These solvents may be used alone or in combination of two or more. A non-aqueous solvent containing a cyclic carbonate and / or a chain carbonate is preferred. (Separator) The separator is used to avoid electrical contact between the positive and negative electrodes. It is also used to avoid an increase in resistance and volume due to the distance between the electrodes. The separator is made of a material having a porous structure and capable of permeating ions. A film-formed material is preferably used. For example, polyethylene, polypropylene, or cellulose is preferable. One side of the separator is preferably in physical contact with the entire surface of the positive electrode mixture layer, and the other side is preferably in physical contact with the entire surface of the negative electrode mixture layer. From the viewpoint of the permeability of the gas generated on the electrode surface and the safety of the battery, it is preferable that the air permeability of the separator measured by the method described in JIS8117 (2009) is 10 sec / 100 cc or more and 100 sec / 100 cc or less. By setting the air permeability of the separator within this range, it is possible to suppress short-circuiting between the positive and negative electrodes, while making it easier for the gas generated on the electrode surface to escape outside the separator without being retained in the electrode group, thereby suppressing an increase in resistance.
[0062] Next, the electrode group will be described. The electrode group includes a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode. The electrode group may be a wound electrode group in which the positive electrode and the negative electrode are wound in a flat or cylindrical shape with a separator therebetween, or a stacked electrode group in which the positive electrode and the negative electrode are stacked with a separator therebetween, or the like.
[0063] The aspect ratio of the electrode group is preferably in the range of 1 to 1.8. By setting the aspect ratio of the electrode group in this range, gas generated near the center of the electrode group can more easily escape to the outside of the electrode group. A more preferable range is 1.1 to 1.8.
[0064] The definition of the aspect ratio will be described with reference to Figs. 3 and 4. The electrode group 200 shown in Fig. 3 is formed by winding a positive electrode, a separator 201, and a negative electrode in a flat shape along the winding direction. The outermost periphery of the electrode group 200 is composed of a separator 201. A positive electrode current collector 202 protrudes from the separator 201 on one side of the winding axis direction, and a negative electrode current collector 203 protrudes from the separator 201 on the other side. In the maximum area surface of the electrode group 200, an intersection point where two diagonal lines of the outermost separator 201 intersect is defined as O. When A is the length passing through the intersection point O and perpendicular to the winding axis, and B is the length passing through O and parallel to the winding axis, the aspect ratio is expressed as B / A. Since gas diffuses in a direction parallel to the winding axis, by setting the aspect ratio (B / A) to be 1 or more and 1.8 or less, gas generated near the center of the electrode group can more easily escape to the outside of the electrode group.
[0065] The electrode group 200 shown in FIG. 4 is formed by winding a positive electrode, a separator 201, and a negative electrode in a flat shape along the winding direction. The outermost periphery of the electrode group 200 is composed of a separator 201. A positive electrode current collector 202 and a negative electrode current collector 203 protrude from the separator 201 on one side of the winding axis direction. In the surface of the electrode group 200 with the largest area, an intersection point where two diagonal lines of the outermost separator 201 intersect is defined as O. When the length passing through the intersection point O and perpendicular to the winding axis is defined as A, and the length passing through the intersection point O and parallel to the winding axis is defined as B, the aspect ratio is expressed as B / A. Since gas diffuses in the direction parallel to the winding axis, by setting the aspect ratio (B / A) to 1 or more and 1.8 or less, gas generated near the center of the electrode group is more likely to escape to the outside of the electrode group.
[0066] The aspect ratio is measured as follows: The exterior material of the battery is disassembled without damaging the internal electrode group, and the electrode group is removed. The above dimensions A and B are measured with digital calipers so as to pass through the center of the part of the removed electrode group covered with the separator (excluding the part exposed from the separator), and B / A is the aspect ratio of the electrode group.
[0067] The wound electrode group is a laminate in which a strip-shaped positive electrode and a strip-shaped negative electrode are laminated with a separator therebetween, and the laminate is further wound. The region on the positive electrode current collector where the positive electrode mixture layer is provided is the positive electrode coated part, and the region on the positive electrode current collector where the positive electrode mixture layer is not provided is the positive electrode uncoated part. The positive electrode uncoated part becomes a positive electrode current collector tab. The region on the negative electrode current collector where the negative electrode mixture layer is provided is the negative electrode coated part, and the region on the negative electrode current collector where the negative electrode mixture layer is not provided is the negative electrode uncoated part. The negative electrode uncoated part becomes a negative electrode current collector tab. The positive electrode, the positive electrode current collector, the positive electrode mixture layer, the negative electrode, the negative electrode current collector, and the negative electrode mixture layer may all be in the form of a strip.
[0068] The positive electrode and the negative electrode extend in a first direction (I) via the separator, and have a band shape having a width in a second direction (II) perpendicular to the first direction. The wound electrode group is preferably housed in an exterior member so as to face in a direction perpendicular to the winding axis.
[0069] The positive and negative electrodes are prepared and then stacked and wound to prepare a wound electrode group. It is preferable to wind the electrodes while adjusting the positions so that the surface of the positive electrode mixture layer faces the surface of the negative electrode mixture layer, that is, so that no non-facing portion is generated in the positive electrode. The outermost layer of the wound electrode group is preferably fixed with insulating tape.
[0070] The battery of the embodiment may further include any of an exterior member, a positive electrode lead, a negative electrode lead, a cover, a positive electrode terminal, a negative electrode terminal, a positive electrode backup lead, a negative electrode backup lead, a positive electrode insulating cover, a negative electrode insulating cover, a positive electrode gasket, a negative electrode gasket, a safety valve, and an electrolyte injection port. The battery of the embodiment may be, for example, a secondary battery capable of charging and discharging. Although the figure shows a square nonaqueous electrolyte battery, the battery is not limited to a square shape.
[0071] Examples of the exterior member include a container made of a laminate film and a container made of metal.
[0072] The laminate film may be a multi-layer film in which a metal layer is interposed between resin films. The metal layer is preferably an aluminum foil or an aluminum alloy foil in order to reduce weight. The resin film may be made of a polymeric material such as polypropylene (PP), polyethylene (PE), nylon, or polyethylene terephthalate (PET). The laminate film may be sealed by heat fusion and molded into the shape of the exterior member. The thickness of the laminate film is preferably, for example, 0.2 mm or less.
[0073] The metal container can be made of aluminum, aluminum alloy, iron, stainless steel, etc. The lid can be made of aluminum, aluminum alloy, iron, stainless steel, etc. It is preferable that the lid and the exterior member are made of the same type of metal. The thickness of the metal container is preferably, for example, 0.5 mm or less.
[0074] The positive electrode current collecting tabs may be bundled with a positive electrode backup lead and electrically connected to a positive electrode terminal via the positive electrode lead, and the negative electrode current collecting tabs may be bundled with a negative electrode backup lead and electrically connected to a negative electrode terminal via the negative electrode lead.
[0075] The positive electrode lead is a conductive member that physically connects the positive electrode terminal and the positive electrode backup lead. The positive electrode lead is a conductive member such as aluminum or an aluminum alloy. The positive electrode lead and the positive electrode backup lead are preferably joined by, for example, laser welding.
[0076] The negative electrode lead is a conductive member that physically connects the negative electrode terminal and the negative electrode backup lead. The negative electrode lead is a conductive member such as aluminum or an aluminum alloy. The negative electrode lead and the negative electrode backup lead are preferably joined by, for example, laser welding.
[0077] The lid is a lid for an exterior member that houses the wound electrode group and has a positive electrode terminal and a negative electrode terminal. The lid includes a positive electrode terminal, a negative electrode terminal, a negative electrode insulating cover, a positive electrode gasket, a negative electrode gasket, a safety valve, and an electrolyte injection port. The lid is a molded member made of a metal or alloy such as aluminum, an aluminum alloy, iron, or stainless steel. The lid and the exterior member are preferably laser welded or bonded with a sealing material such as an adhesive resin.
[0078] The positive electrode terminal is an electrode terminal for the positive electrode of the secondary battery provided on the lid. The positive electrode terminal is made of a conductive material such as aluminum or an aluminum alloy. The positive electrode terminal is fixed to the lid via an insulating positive electrode gasket. The positive electrode terminal is electrically connected to the positive electrode via a positive electrode lead and a positive electrode backup lead.
[0079] The negative electrode terminal is an electrode terminal for the negative electrode of the secondary battery provided on the lid. The negative electrode terminal is made of a conductive material such as aluminum or an aluminum alloy. The negative electrode terminal is fixed to the lid via an insulating negative electrode gasket. The negative electrode terminal is electrically connected to the negative electrode via a negative electrode lead and a negative electrode backup lead.
[0080] The positive electrode backup lead is a conductive member that is formed by bundling positive electrode current collecting tabs and fixing them to the positive electrode lead. The positive electrode backup lead and the positive electrode current collecting tabs are preferably joined by ultrasonic bonding.
[0081] The negative electrode backup lead is a conductive member that is formed by bundling negative electrode current collecting tabs and fixing them to the negative electrode lead. The negative electrode backup lead and the negative electrode current collecting tabs are preferably joined by ultrasonic bonding.
[0082] The positive electrode insulating cover is an insulating member that covers the positive electrode lead and the positive electrode backup lead. The positive electrode insulating cover is joined to one end of the wound electrode group including the positive electrode current collecting tab. The positive electrode insulating cover is preferably an insulating and heat-resistant member. As the positive electrode insulating cover, a resin molded body, a molded body of a material mainly made of paper, or a member in which a molded body of a material mainly made of paper is covered with a resin is preferable. As the resin, polyethylene resin or fluororesin is preferably used. The shape of the positive electrode insulating cover is such that the positive electrode lead and the positive electrode backup lead are in contact with the exterior member. By using the positive electrode insulating cover, the positive electrode and the exterior member are insulated, and the current collecting tab area (current collecting tab, lead, backup lead) can be protected from external impact.
[0083] The negative electrode insulating cover is an insulating member that covers the negative electrode lead and the negative electrode backup lead. The negative electrode insulating cover is fitted to one end of the wound electrode group, including the negative electrode current collecting tab. The material and shape of the negative electrode insulating cover are the same as those of the positive electrode insulating cover. A description of the common features between the positive electrode insulating cover and the negative electrode insulating cover will be omitted.
[0084] The positive electrode gasket is a member that insulates the positive electrode terminal from the exterior member. The positive electrode gasket is preferably a resin molded body that is solvent-resistant and flame-retardant. For example, polyethylene resin or fluororesin is used for the positive electrode gasket.
[0085] The negative electrode gasket is a member that insulates the negative electrode terminal from the exterior member. The negative electrode gasket is preferably a resin molded body that is solvent-resistant and flame-retardant. For example, polyethylene resin or fluororesin is used for the negative electrode gasket.
[0086] The safety valve is a member provided in the lid and functions as a pressure reducing valve that reduces the pressure inside the exterior member when the internal pressure inside the exterior member increases. Although it is preferable to provide a safety valve, it may be omitted in consideration of conditions such as the protection mechanism of the battery and the electrode material.
[0087] The electrolyte injection port is a hole for injecting an electrolyte, and is preferably sealed with a resin or the like after the electrolyte is injected.
[0088] Although not shown in the drawing, it is preferable that each member is fixed or connected using an insulating adhesive tape.
[0089] Next, specific examples of the battery according to the embodiment will be described with reference to the drawings.
[0090] First, a first example of a nonaqueous electrolyte battery according to the embodiment will be described with reference to FIGS.
[0091] Fig. 5 is a partially cutaway perspective view of an example of a nonaqueous electrolyte battery according to an embodiment of the present invention, Fig. 6 is an enlarged cross-sectional view of a portion A of the nonaqueous electrolyte battery shown in Fig. 5.
[0092] 5 and 6 includes a flat electrode group 1 and an exterior member 7 made of a laminate film. The flat electrode group 1 includes a negative electrode 2, a positive electrode 3, and a separator 4. The flat electrode group 1 is formed by winding the negative electrode 2 and the positive electrode 3 with the separator 4 interposed therebetween into a flat shape.
[0093] As shown in FIG. 6, the negative electrode 2 includes a negative electrode current collector 2a and a negative electrode active material-containing layer 2b supported on the negative electrode current collector 2a. As shown in FIG. 6, in the outermost portion of the negative electrode 2, the negative electrode active material-containing layer 2b is not supported on the main surface of the negative electrode current collector 2a that does not face the positive electrode 3. In the other portion of the negative electrode 2, the negative electrode active material-containing layer 2b is supported on both main surfaces of the negative electrode current collector. As shown in FIG. 6, the positive electrode 3 includes a positive electrode current collector 3a and a positive electrode active material-containing layer 3b supported on the two main surfaces of the positive electrode current collector 3a.
[0094] A band-shaped negative electrode terminal 5 is electrically connected to the negative electrode 2. A band-shaped positive electrode terminal 6 is electrically connected to the positive electrode 3.
[0095] The electrode group 1 is housed in an exterior member 7 made of a laminate film with the ends of the negative electrode terminal 5 and the positive electrode terminal 6 extending from the exterior member 7. A non-aqueous electrolyte (not shown) is housed in the exterior member 7 made of laminate film. The non-aqueous electrolyte is impregnated into the electrode group 1. The exterior member 7 made of laminate film is sealed by heat-sealing one end of the exterior member 7 with the negative electrode terminal 5 and the positive electrode terminal 6 sandwiched therebetween and the end and two other ends perpendicular to the end.
[0096] Next, another example of the battery according to the embodiment will be described in detail with reference to Fig. 7. Fig. 7 is a partially cutaway perspective view showing another example of the battery according to the embodiment.
[0097] The battery 100 shown in FIG. 7 differs from the battery 100 shown in FIGS. 5 and 6 in that the exterior member is composed of a metal container 17a and a sealing plate 17b.
[0098] The flat electrode group 1 includes a negative electrode, a positive electrode, and a separator, similar to the electrode group 1 in the battery 100 shown in Figures 5 and 6. The electrode group 1 has a similar structure between Figures 5 and 7. However, in Figure 7, instead of the negative electrode terminal 5 and the positive electrode terminal 6, a negative electrode lead 15a and a positive electrode lead 16a are electrically connected to the negative electrode and the positive electrode, respectively, as described below.
[0099] In the battery 100 shown in Fig. 7, such an electrode group 1 is housed in a metal container 17a. The metal container 17a further houses an electrolyte (not shown). The metal container 17a is sealed by a metal sealing plate 17b. The metal container 17a and the sealing plate 17b constitute, for example, an exterior can as an exterior member.
[0100] One end of the negative electrode lead 15a is electrically connected to the negative electrode current collector, and the other end is electrically connected to the negative electrode terminal 15. One end of the positive electrode lead 16a is electrically connected to the positive electrode current collector, and the other end is electrically connected to a positive electrode terminal 16 fixed to a sealing plate 17b. The positive electrode terminal 16 is fixed to the sealing plate 17b via an insulating member 17c. The positive electrode terminal 16 and the sealing plate 17b are electrically insulated by the insulating member 17c.
[0101] 8 and 9 show a battery including a stacked electrode group as yet another example of the battery. Fig. 8 is a partially cutaway perspective view showing yet another example of the battery according to the embodiment. Fig. 9 is an enlarged cross-sectional view of part B of the battery shown in Fig. 8.
[0102] The battery 100 of the example shown in Figures 8 and 9 includes an electrode group 1 shown in Figures 8 and 9, an outer container 7 shown in Figures 8 and 9, a positive electrode terminal 6 shown in Figures 8 and 9, and a negative electrode terminal 5 shown in Figure 8.
[0103] The electrode group 1 shown in FIGS. 8 and 9 includes a plurality of positive electrodes 3, a plurality of negative electrodes 2, and one separator 4.
[0104] As shown in Fig. 9, each positive electrode 3 includes a positive electrode current collector 3a and a positive electrode active material-containing layer 3b formed on both sides of the positive electrode current collector 3a. As shown in Fig. 9, the positive electrode current collector 3a includes a portion on the surface where the positive electrode active material-containing layer 3b is not formed. This portion serves as a positive electrode current collector tab 3c.
[0105] Each negative electrode 2 includes a negative electrode current collector 2a and a negative electrode active material-containing layer 2b formed on both sides of the negative electrode current collector 2a. The negative electrode current collector 2a also includes a portion on the surface where the negative electrode active material-containing layer 2b is not formed (not shown). This portion functions as a negative electrode current collector tab.
[0106] As shown in part in Fig. 9, the separator 4 is zigzag folded. A positive electrode 3 or a negative electrode 2 is disposed in the space defined by the opposing faces of the zigzag folded separator 4. As a result, the positive electrode 3 and the negative electrode 2 are stacked such that the positive electrode active material-containing layer 3b and the negative electrode active material-containing layer 2b face each other with the separator 4 interposed therebetween, as shown in Fig. 9. In this manner, an electrode group 1 is formed.
[0107] As shown in FIG. 9, the positive electrode current collector tab 3c of the electrode group 1 extends beyond the respective ends of the positive electrode active material-containing layer 3b and the negative electrode active material-containing layer 2b. As shown in FIG. 9, these positive electrode current collector tabs 3c are joined together and connected to a positive electrode terminal 6. Although not shown, the negative electrode current collector tab of the electrode group 1 also extends beyond the other end of each of the positive electrode active material-containing layer 3b and the negative electrode active material-containing layer 2b. Although not shown, these negative electrode current collector tabs are joined together and connected to a negative electrode terminal 5 shown in FIG. 8.
[0108] Such an electrode group 1 is housed in an exterior member made of an exterior container 7 made of a laminate film, as shown in FIGS.
[0109] The outer container 7 is formed of an aluminum-containing laminate film consisting of an aluminum foil 71 and resin films 72 and 73 formed on both sides of the aluminum foil 71. The aluminum-containing laminate film forming the outer container 7 is folded at the folding portion 7d so that the resin film 72 faces inward, and contains the electrode group 1. As shown in Figs. 8 and 9, at the peripheral portion 7b of the outer container 7, the facing portions of the resin film 72 sandwich the positive electrode terminal 6 therebetween. Similarly, at the peripheral portion 7c of the outer container 7, the facing portions of the resin film 72 sandwich the negative electrode terminal 5 therebetween. The positive electrode terminal 6 and the negative electrode terminal 5 extend from the outer container 7 in opposite directions.
[0110] At peripheral portions 7a, 7b and 7c of the outer container 7 except for the portions sandwiching the positive electrode terminal 6 and the negative electrode terminal 5, portions of the resin film 72 facing each other are heat-sealed.
[0111] In the battery 100, in order to improve the bonding strength between the positive terminal 6 and the resin film 72, as shown in FIG. 9, an insulating film 9 is provided between the positive terminal 6 and the resin film 72. In addition, in the peripheral portion 7b, the positive terminal 6 and the insulating film 9 are heat-sealed, and the resin film 72 and the insulating film 9 are heat-sealed. Similarly, although not shown, an insulating film 9 is provided between the negative terminal 5 and the resin film 72. In addition, in the peripheral portion 7c, the negative terminal 5 and the insulating film 9 are heat-sealed, and the resin film 72 and the insulating film 9 are heat-sealed. That is, in the battery 100 shown in FIG. 8, all of the peripheral portions 7a, 7b, and 7c of the outer container 7 are heat-sealed.
[0112] The outer container 7 further contains an electrolyte (not shown). The electrode group 1 is impregnated with the electrolyte.
[0113] In the battery 100 shown in Figures 8 and 9, as shown in Figure 9, a plurality of positive electrode current collecting tabs 3c are gathered together in the lowest layer of the electrode group 1. Similarly, although not shown, a plurality of negative electrode current collecting tabs are gathered together in the lowest layer of the electrode group 1. However, for example, a plurality of positive electrode current collecting tabs 3c and a plurality of negative electrode current collecting tabs can also be gathered together in one near the middle of the electrode group 1 and connected to the positive electrode terminal 6 and the negative electrode terminal 5, respectively.
[0114] According to the battery of the second embodiment described above, since it contains the electrode of the first embodiment, it is possible to realize a battery with high capacity and excellent charge / discharge cycle performance.
[0115] (Third embodiment) According to a third embodiment, a battery pack is provided, the battery pack including the battery according to the second embodiment.
[0116] The battery pack according to the embodiment may include a plurality of batteries. The plurality of batteries may be electrically connected in series or in parallel. Alternatively, the plurality of batteries may be electrically connected in a combination of series and parallel. That is, the battery pack according to the embodiment may include an assembled battery. There may be a plurality of assembled batteries. The assembled batteries may be electrically connected in series, in parallel, or in a combination of series and parallel.
[0117] Hereinafter, an example of a battery pack according to the embodiment will be described with reference to Fig. 10 and Fig. 11. Fig. 10 is an exploded perspective view showing an example of a battery pack according to the embodiment. Fig. 11 is a block diagram showing an example of an electric circuit of the battery pack shown in Fig. 10.
[0118] 10 and 11 includes a plurality of unit cells 21. The unit cells 21 may be, for example, the flat-type battery 100 according to the embodiment described with reference to FIG.
[0119] A plurality of unit cells 21 are stacked such that the negative electrode terminals 5 and positive electrode terminals 6 extending outward are aligned in the same direction, and are fastened together with adhesive tape 22 to form an assembled battery 23. These unit cells 21 are electrically connected in series with each other as shown in FIG.
[0120] The printed wiring board 24 is disposed so as to face the side surface from which the negative electrode terminal 5 and the positive electrode terminal 6 of the single cell 21 extend. A thermistor 25, a protection circuit 26, and a terminal 27 for supplying electricity to an external device are mounted on the printed wiring board 24, as shown in Fig. 11. An insulating plate (not shown) is attached to the surface of the printed wiring board 24 facing the assembled battery 23 in order to prevent unnecessary connection with the wiring of the assembled battery 23.
[0121] The positive electrode lead 28 is connected to the positive electrode terminal 6 located in the bottom layer of the battery pack 23, and its tip is inserted into and electrically connected to a positive electrode connector 29 of the printed wiring board 24. The negative electrode lead 30 is connected to the negative electrode terminal 5 located in the top layer of the battery pack 23, and its tip is inserted into and electrically connected to a negative electrode connector 31 of the printed wiring board 24. These connectors 29 and 31 are connected to the protection circuit 26 through wiring 32 and 33 formed on the printed wiring board 24.
[0122] The thermistor 25 detects the temperature of the cell 21, and the detection signal is sent to the protection circuit 26. The protection circuit 26 can cut off the positive side wiring 34a and the negative side wiring 34b between the protection circuit 26 and the terminal 27 for supplying electricity to the external device under a predetermined condition. An example of the predetermined condition is when the temperature detected by the thermistor 25 becomes equal to or higher than a predetermined temperature. Another example of the predetermined condition is when overcharging, overdischarging, or overcurrent of the cell 21 is detected. This detection of overcharging, etc. is performed for each cell 21 or the entire battery pack 23. When detecting each cell 21, the battery voltage may be detected, or the positive electrode potential or the negative electrode potential may be detected. In the latter case, a lithium electrode used as a reference electrode is inserted into each cell 21. In the battery pack 20 of FIG. 10 and FIG. 11, wiring 35 for voltage detection is connected to each cell 21. A detection signal is transmitted to the protection circuit 26 through these wirings 35.
[0123] Protective sheets 36 made of rubber or resin are disposed on the three side surfaces of the battery pack 23 excluding the side surfaces from which the positive electrode terminal 6 and the negative electrode terminal 5 protrude.
[0124] The battery pack 23 is housed in a container 37 together with the protective sheets 36 and the printed wiring board 24. That is, the protective sheets 36 are arranged on both inner surfaces along the long sides and the inner surface along the short side of the container 37, and the printed wiring board 24 is arranged on the other inner surface along the short side on the opposite side across the battery pack 23. The battery pack 23 is located in a space surrounded by the protective sheets 36 and the printed wiring board 24. A lid 38 is attached to the top surface of the container 37.
[0125] Note that heat shrink tape may be used to fix the battery pack 23 instead of the adhesive tape 22. In this case, protective sheets are placed on both sides of the battery pack, the heat shrink tape is wrapped around it, and then the heat shrink tape is thermally shrunk to bind the battery pack.
[0126] 10 and 11 show a configuration in which the cells 21 are electrically connected in series, but they may be electrically connected in parallel to increase the battery capacity. Furthermore, assembled battery packs may be electrically connected in series and / or parallel.
[0127] The battery pack according to the embodiment may be modified as appropriate depending on the application. The battery pack according to the embodiment is preferably used in applications where cycle performance in charging and discharging a large current is desired. Specific applications include power sources for digital cameras, and in-vehicle applications such as two- to four-wheel hybrid electric vehicles, two- to four-wheel electric vehicles, and power-assisted bicycles. In particular, the battery pack according to the embodiment is preferably used in-vehicle.
[0128] The battery pack according to the third embodiment includes the battery according to the second embodiment, and therefore has a high capacity and an excellent life performance. [Example] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the examples listed below as long as it does not depart from the gist of the invention.
[0129] Example 1 1. Fabrication of Non-aqueous Electrolyte Battery In Example 1, a square nonaqueous electrolyte battery was fabricated as follows. [Preparation of positive electrode] As a positive electrode active material, the average particle size D 1 is 20μm, LiNi 0.8 Co 0.1 Mn 0.1 O 2 The lithium nickel cobalt manganese composite oxide particles (first particles) represented by the average particle size D 2 is 5μm, LiNi 0.8 Co 0.1 Mn 0.1 O 2 Lithium nickel cobalt manganese composite oxide particles (secondary particles) represented by the average particle size D 2 is 7 μm, and LiCoO 2 The particle size of the first particles was within a range of 8 μm or more and 25 μm or less. The particle size of the second particles was within a range of 2 μm or more and 6 μm or less. The particle size of the lithium cobalt composite oxide particles was within a range of 3 μm or more and 13 μm or less.
[0130] A positive electrode active material consisting of 69% by weight of the first particles, 11% by weight of the second particles, and 20% by weight of the lithium-cobalt composite oxide particles was dry-mixed with 93% by weight of acetylene black as a conductive agent and 2% by weight of graphite. The resulting mixed powder and 2% by weight of polyvinylidene fluoride (PVdF) as a binder were suspended in N-methylpyrrolidone (NMP) to a solid content ratio of 82.3% by weight, and the mixture was kneaded to prepare a first slurry.
[0131] N-methylpyrrolidone was added to the first slurry and the mixture was stirred and diluted to prepare a second slurry having a solid content of 67.0% by weight.
[0132] An aluminum foil having a thickness of 12 μm was prepared as a positive electrode current collector. The positive electrode current collector had a band shape extending in a first direction (I) and having a width in a second direction (II) perpendicular to the first direction. The positive electrode second slurry prepared by the above procedure was applied to both sides of the positive electrode current collector so that the thickness of the positive electrode mixture layer was 100 μm, and dried to obtain a positive electrode mixture layer. When applying the positive electrode second slurry, a band-shaped slurry uncoated portion extending in the first direction (I) was left for 10 mm on a part of the surface of the positive electrode current collector to form a positive electrode current collector tab. After drying, the positive electrode mixture layer was cut to have a width of 90 mm. After cutting, the electrode was rolled with a constant load to prepare a positive electrode. [Preparation of negative electrode] Spinel-type lithium titanate (Li) as a negative electrode active material 4 Ti 5 O 12 The lithium titanate, PVdF as a binder, and graphite as a conductive agent were suspended in N-methylpyrrolidone to obtain a slurry for preparing a negative electrode. The mixture ratios of lithium titanate, PVdF, and graphite added to N-methylpyrrolidone were 95% by weight, 2% by weight, and 3% by weight, respectively.
[0133] An aluminum foil having a thickness of 12 μm was prepared as the negative electrode current collector. The negative electrode current collector had a band shape extending in a first direction (I) and having a width in a second direction (II) perpendicular to the first direction. The negative electrode slurry prepared by the above procedure was applied to both sides and dried. When applying the negative electrode slurry, a band-shaped slurry-unapplied portion extending in the first direction (I) was left for 10 mm on a part of the surface of the negative electrode current collector to form a negative electrode current collector tab. After drying, the negative electrode current collector was cut so that the width of the active material layer on the negative electrode current collector was 95 mm. After cutting, the electrode was rolled with a constant load to prepare a negative electrode. [Fabrication of wound electrode group] As the separator, a cellulose nonwoven fabric having a thickness of 10 μm and an air permeability of 60 sec / 100 cc measured by the method described in JIS8117 (2009) was prepared. The positive electrode and negative electrode thus obtained were wound around an axis extending in the width direction of the positive electrode and negative electrode through the separator. At this time, 40 turns of the positive electrode and 41 turns of the negative electrode were wound while adjusting the position so that the positive electrode mixture layer and the negative electrode mixture layer do not protrude from the separator, that is, so that the surface of the positive electrode mixture layer faces the surface of the negative electrode mixture layer, that is, so that the surface of the positive electrode mixture layer does not protrude from the surface of the negative electrode mixture layer. An insulating tape having a thickness of 50 μm was attached to the surface of the negative electrode mixture layer at the outermost periphery of the electrode group to fix the electrode group. The electrode group prepared by winding as described above was pressed to obtain a flat wound electrode group. The positive electrode current collector tabs were bundled by ultrasonic welding between the tabs, and the negative electrode current collector tabs were bundled by ultrasonic welding between the tabs. The obtained electrode group had the structure shown in Figure 4, and the aspect ratio represented by B / A was 1.1. [Battery assembly] The flat wound electrode group and the nonaqueous electrolyte thus obtained were housed in an aluminum rectangular container with a bottom having an opening. At this time, the positive electrode current collecting tab and the negative electrode current collecting tab were made to extend from the end face of the electrode group facing the opening. Next, a rectangular sealing plate made of aluminum was prepared. The sealing plate was provided with three openings (not shown). A rectangular positive electrode terminal was fitted and fixed in one of the three openings. A rectangular negative electrode terminal was fitted and fixed in the other of the three openings via an insulating gasket. The remaining one of the three openings was an injection port for injecting the electrolyte. Next, one end of the positive electrode terminal and the positive electrode current collecting tab of the electrode group were electrically connected by laser welding. Similarly, one end of the negative electrode terminal and the negative electrode current collecting tab of the electrode group were electrically connected by laser welding. Next, the peripheral portion of the sealing plate was welded to the container so as to close the opening of the container.
[0134] Next, a non-aqueous electrolyte was prepared. The non-aqueous electrolyte was prepared by mixing propylene carbonate (PC) and diethyl carbonate (DEC) in a volume ratio of 1:1, dissolving lithium hexafluorophosphate (LiPF6 was dissolved at a concentration of 1.2 mol / L.
[0135] Next, the non-aqueous electrolyte prepared as described above was poured into the container through the electrolyte injection port provided in the sealing plate, and a sealing lid was welded to the periphery of the electrolyte injection port to assemble the battery. Example 2 A battery was assembled in the same manner as in Example 1, except that the following positive electrode was used.
[0136] As a positive electrode active material, the average particle size D 1 is 14μm, LiNi 0.8 Co 0.1 Mn 0.1 O 2 The lithium nickel cobalt manganese composite oxide particles (first particles) represented by the average particle size D 2 is 5μm, LiNi 0.8 Co 0.1 Mn 0.1 O 2 Lithium nickel cobalt manganese composite oxide particles (second particles) represented by LiCoO 2 The particle size of the first particles was within a range of 8 μm or more and 20 μm or less. The particle size of the second particles was within a range of 2 μm or more and 6 μm or less. The particle size of the lithium cobalt composite oxide particles was within a range of 3 μm or more and 13 μm or less.
[0137] A positive electrode active material consisting of 65% by weight of the first particles, 15% by weight of the second particles, and 20% by weight of the lithium-cobalt composite oxide particles was dry-mixed with 93% by weight of acetylene black as a conductive agent and 2% by weight of graphite. The resulting mixed powder was suspended in N-methylpyrrolidone (NMP) with 2% by weight of polyvinylidene fluoride (PVdF) as a binder so that the solid content ratio was 82.3% by weight, and the mixture was kneaded to prepare a first slurry.
[0138] N-methylpyrrolidone was added to the first slurry and the mixture was stirred and diluted to prepare a second slurry having a solid content of 67.0% by weight.
[0139] An aluminum foil having a thickness of 12 μm was prepared as a positive electrode current collector. The positive electrode current collector had a band shape extending in a first direction (I) and having a width in a second direction (II) perpendicular to the first direction. The positive electrode second slurry prepared by the above procedure was applied to both sides of the positive electrode current collector so that the thickness of the positive electrode mixture layer was 40 μm, and dried to obtain a positive electrode mixture layer. When applying the positive electrode second slurry, a band-shaped slurry uncoated portion extending in the first direction (I) was left for 10 mm on a part of the surface of the positive electrode current collector to form a positive electrode current collector tab. After drying, the positive electrode mixture layer was cut to have a width of 90 mm. After cutting, the electrode was rolled with a constant load to prepare a positive electrode. Example 3 A battery was assembled in the same manner as in Example 1, except that the following positive electrode was used.
[0140] As a positive electrode active material, the average particle size D 1 is 20μm, LiNi 0.8 Co 0.1 Mn 0.1 O 2 The lithium nickel cobalt manganese composite oxide particles (first particles) represented by the average particle size D 2 is 5μm, LiNi 0.8 Co 0.1 Mn 0.1 O 2 Lithium nickel cobalt manganese composite oxide particles (second particles) represented by LiCoO 2 The particle size of the first particles was within a range of 8 μm or more and 25 μm or less. The particle size of the second particles was within a range of 2 μm or more and 6 μm or less. The particle size of the lithium cobalt composite oxide particles was within a range of 3 μm or more and 13 μm or less.
[0141] A positive electrode active material consisting of 78% by weight of the first particles, 2% by weight of the second particles, and 20% by weight of lithium-cobalt composite oxide particles was dry-mixed with 93% by weight of acetylene black as a conductive agent and 2% by weight of graphite. The resulting mixed powder was suspended in N-methylpyrrolidone (NMP) with 2% by weight of polyvinylidene fluoride (PVdF) as a binder so that the solid content ratio was 82.3% by weight, and the mixture was kneaded to prepare a first slurry.
[0142] N-methylpyrrolidone was added to the first slurry and the mixture was stirred and diluted to prepare a second slurry having a solid content of 67.0% by weight.
[0143] An aluminum foil having a thickness of 12 μm was prepared as a positive electrode current collector. The positive electrode current collector had a band shape extending in a first direction (I) and having a width in a second direction (II) perpendicular to the first direction. The positive electrode second slurry prepared by the above procedure was applied to both sides of the positive electrode current collector so that the thickness of the positive electrode mixture layer was 100 μm, and dried to obtain a positive electrode mixture layer. When applying the positive electrode second slurry, a band-shaped slurry uncoated portion extending in the first direction (I) was left for 10 mm on a part of the surface of the positive electrode current collector to form a positive electrode current collector tab. After drying, the positive electrode mixture layer was cut to have a width of 90 mm. After cutting, the electrode was rolled with a constant load to prepare a positive electrode. Example 4 A battery was assembled in the same manner as in Example 1, except that the following positive electrode was used.
[0144] As a positive electrode active material, the average particle size D 1 is 14μm, LiNi 0.8 Co 0.1 Mn 0.1 O 2 The lithium nickel cobalt manganese composite oxide particles (first particles) represented by the average particle size D 2 is 1μm, LiNi 0.8 Co 0.1 Mn 0.1 O 2 Lithium nickel cobalt manganese composite oxide particles (second particles) represented by LiCoO 2The particle size of the first particles was within the range of 8 μm or more and 20 μm or less. The particle size of the second particles was within the range of 0.5 μm or more and 1.4 μm or less. The particle size of the lithium cobalt composite oxide particles was within the range of 3 μm or more and 13 μm or less.
[0145] A positive electrode active material consisting of 78% by weight of the first particles, 2% by weight of the second particles, and 20% by weight of lithium-cobalt composite oxide particles was dry-mixed with 93% by weight of acetylene black as a conductive agent and 2% by weight of graphite. The resulting mixed powder was suspended in N-methylpyrrolidone (NMP) with 2% by weight of polyvinylidene fluoride (PVdF) as a binder so that the solid content ratio was 82.3% by weight, and the mixture was kneaded to prepare a first slurry.
[0146] N-methylpyrrolidone was added to the first slurry and the mixture was stirred and diluted to prepare a second slurry having a solid content of 67.0% by weight.
[0147] An aluminum foil having a thickness of 12 μm was prepared as a positive electrode current collector. The positive electrode current collector had a band shape extending in a first direction (I) and having a width in a second direction (II) perpendicular to the first direction. The positive electrode second slurry prepared by the above procedure was applied to both sides of the positive electrode current collector so that the thickness of the positive electrode mixture layer was 100 μm, and dried to obtain a positive electrode mixture layer. When applying the positive electrode second slurry, a band-shaped slurry uncoated portion extending in the first direction (I) was left for 10 mm on a part of the surface of the positive electrode current collector to form a positive electrode current collector tab. After drying, the positive electrode mixture layer was cut to have a width of 90 mm. After cutting, the electrode was rolled with a constant load to prepare a positive electrode. Example 5 A battery was assembled in the same manner as in Example 1, except that the following positive electrode was used.
[0148] As a positive electrode active material, the average particle size D 1 is 14μm, LiNi 0.8 Co 0.1 Mn 0.1 O 2The lithium nickel cobalt manganese composite oxide particles (first particles) represented by the average particle size D 2 is 6μm, LiNi 0.8 Co 0.1 Mn 0.1 O 2 Lithium nickel cobalt manganese composite oxide particles (second particles) represented by LiCoO 2 The particle size of the first particles was within a range of 8 μm or more and 20 μm or less. The particle size of the second particles was within a range of 4.5 μm or more and 7 μm or less. The particle size of the lithium cobalt composite oxide particles was within a range of 3 μm or more and 13 μm or less.
[0149] A positive electrode active material consisting of 73% by weight of the first particles, 7% by weight of the second particles, and 20% by weight of lithium-cobalt composite oxide particles was dry-mixed with 93% by weight of acetylene black as a conductive agent and 2% by weight of graphite. The resulting mixed powder was suspended in N-methylpyrrolidone (NMP) with 2% by weight of polyvinylidene fluoride (PVdF) as a binder so that the solid content ratio was 82.3% by weight, and the mixture was kneaded to prepare a first slurry.
[0150] N-methylpyrrolidone was added to the first slurry and the mixture was stirred and diluted to prepare a second slurry having a solid content of 67.0% by weight.
[0151] An aluminum foil having a thickness of 12 μm was prepared as a positive electrode current collector. The positive electrode current collector had a band shape extending in a first direction (I) and having a width in a second direction (II) perpendicular to the first direction. The positive electrode second slurry prepared by the above procedure was applied to both sides of the positive electrode current collector so that the thickness of the positive electrode mixture layer was 100 μm, and dried to obtain a positive electrode mixture layer. When applying the positive electrode second slurry, a band-shaped slurry uncoated portion extending in the first direction (I) was left for 10 mm on a part of the surface of the positive electrode current collector to form a positive electrode current collector tab. After drying, the positive electrode mixture layer was cut to have a width of 90 mm. After cutting, the electrode was rolled with a constant load to prepare a positive electrode. Example 6 A battery was assembled in the same manner as in Example 1, except that the following positive electrode was used.
[0152] As a positive electrode active material, the average particle size D 1 is 19μm, LiNi 0.5 Co 0.2 Mn 0.3 O 2 The lithium nickel cobalt manganese composite oxide particles (first particles) represented by the average particle size D 2 is 5μm, LiNi 0.5 Co 0.2 Mn 0.3 O 2 Lithium nickel cobalt manganese composite oxide particles (second particles) represented by LiCoO 2 The particle size of the first particles was within a range of 8 μm or more and 23 μm or less. The particle size of the second particles was within a range of 2 μm or more and 6 μm or less. The particle size of the lithium cobalt composite oxide particles was within a range of 3 μm or more and 13 μm or less.
[0153] A positive electrode active material consisting of 75% by weight of the first particles, 5% by weight of the second particles, and 20% by weight of lithium-cobalt composite oxide particles was dry-mixed with 93% by weight of acetylene black as a conductive agent and 2% by weight of graphite. The resulting mixed powder was suspended in N-methylpyrrolidone (NMP) with 2% by weight of polyvinylidene fluoride (PVdF) as a binder so that the solid content ratio was 82.3% by weight, and the mixture was kneaded to prepare a first slurry.
[0154] N-methylpyrrolidone was added to the first slurry and the mixture was stirred and diluted to prepare a second slurry having a solid content of 65.0% by weight.
[0155] An aluminum foil having a thickness of 12 μm was prepared as a positive electrode current collector. The positive electrode current collector had a band shape extending in a first direction (I) and having a width in a second direction (II) perpendicular to the first direction. The positive electrode second slurry prepared by the above procedure was applied to both sides of the positive electrode current collector so that the thickness of the positive electrode mixture layer was 120 μm, and dried to obtain a positive electrode mixture layer. When applying the positive electrode second slurry, a band-shaped slurry uncoated portion extending in the first direction (I) was left for 10 mm on a part of the surface of the positive electrode current collector to form a positive electrode current collector tab. After drying, the positive electrode mixture layer was cut to have a width of 90 mm. After cutting, the electrode was rolled with a constant load to prepare a positive electrode. Example 7 A battery was assembled in the same manner as in Example 1, except that the following positive electrode was used.
[0156] As a positive electrode active material, the average particle size D 1 is 13μm, LiMn 2 O 4 The lithium manganese composite oxide particles (first particles) represented by the average particle diameter D 2 is 3μm, LiMn 2 O 4 Lithium manganese composite oxide particles (second particles) represented by LiCoO 2 The particle size of the first particles was within a range of 8 μm or more and 18 μm or less. The particle size of the second particles was within a range of 1.5 μm or more and 5 μm or less. The particle size of the lithium cobalt composite oxide particles was within a range of 3 μm or more and 13 μm or less.
[0157] A positive electrode active material consisting of 74% by weight of the first particles, 6% by weight of the second particles, and 20% by weight of the lithium-cobalt composite oxide particles was dry-mixed with 93% by weight of the positive electrode active material, 3% by weight of acetylene black as a conductive agent, and 2% by weight of graphite. The resulting mixed powder was suspended in N-methylpyrrolidone (NMP) with 2% by weight of polyvinylidene fluoride (PVdF) as a binder so that the solid content ratio was 82.3% by weight, and the mixture was kneaded to prepare a first slurry.
[0158] N-methylpyrrolidone was added to the first slurry and the mixture was stirred and diluted to prepare a second slurry having a solid content of 65.0% by weight.
[0159] An aluminum foil having a thickness of 12 μm was prepared as a positive electrode current collector. The positive electrode current collector had a band shape extending in a first direction (I) and having a width in a second direction (II) perpendicular to the first direction. The positive electrode second slurry prepared by the above procedure was applied to both sides of the positive electrode current collector so that the thickness of the positive electrode mixture layer was 150 μm, and dried to obtain a positive electrode mixture layer. When applying the positive electrode second slurry, a band-shaped slurry uncoated portion extending in the first direction (I) was left for 10 mm on a part of the surface of the positive electrode current collector to form a positive electrode current collector tab. After drying, the positive electrode mixture layer was cut to have a width of 90 mm. After cutting, the electrode was rolled with a constant load to prepare a positive electrode. Example 8
[0160] A battery was assembled in the same manner as in Example 1, except that the positive electrode mixture layer was cut to a width of 82 mm, the active material layer on the negative electrode current collector was cut to a width of 87 mm, and the electrode group was wound so that the aspect ratio was the value shown in Table 1. Example 9
[0161] A battery was assembled in the same manner as in Example 1, except that the positive electrode mixture layer was cut to a width of 162 mm, the active material layer on the negative electrode current collector was cut to a width of 171 mm, and the electrode group was wound so that the aspect ratio was the value shown in Table 1. Example 10
[0162] A battery was assembled in the same manner as in Example 1, except that a separator with an air permeability of 20 sec / 100 cc was used. Example 11
[0163] A battery was assembled in the same manner as in Example 1, except that a separator with an air permeability of 100 sec / 100 cc was used. Comparative Example 1 A battery was assembled in the same manner as in Example 1, except that the following positive electrode was used.
[0164] As a positive electrode active material, the average particle size D 1 is 12μm, LiNi 0.8 Co 0.1 Mn 0.1 O 2 The lithium nickel cobalt manganese composite oxide particles (first particles) represented by the average particle size D 2 is 5μm, LiNi 0.8 Co 0.1 Mn 0.1 O 2 Lithium nickel cobalt manganese composite oxide particles (second particles) represented by LiCoO 2 The particle size of the first particles was within a range of 8 μm or more and 12 μm or less. The particle size of the second particles was within a range of 2 μm or more and 6 μm or less. The particle size of the lithium cobalt composite oxide particles was within a range of 3 μm or more and 13 μm or less.
[0165] A positive electrode active material consisting of 36% by weight of the first particles, 44% by weight of the second particles, and 20% by weight of lithium-cobalt composite oxide particles was dry-mixed with 93% by weight of acetylene black as a conductive agent and 2% by weight of graphite. The resulting mixed powder was suspended in N-methylpyrrolidone (NMP) with 2% by weight of polyvinylidene fluoride (PVdF) as a binder so that the solid content ratio was 82.3% by weight to prepare a slurry.
[0166] An aluminum foil having a thickness of 12 μm was prepared as a positive electrode current collector. The positive electrode current collector had a band shape extending in a first direction (I) and having a width in a second direction (II) perpendicular to the first direction. The positive electrode second slurry prepared by the above procedure was applied to both sides of the positive electrode current collector so that the thickness of the positive electrode mixture layer was 40 μm, and dried to obtain a positive electrode mixture layer. When applying the positive electrode second slurry, a band-shaped slurry uncoated portion extending in the first direction (I) was left for 10 mm on a part of the surface of the positive electrode current collector to form a positive electrode current collector tab. After drying, the positive electrode mixture layer was cut to have a width of 90 mm. After cutting, the electrode was rolled with a constant load to prepare a positive electrode. Comparative Example 2
[0167] As a positive electrode active material, the average particle size D 1 is 10μm, LiNi 0.8 Co 0.1 Mn 0.1 O 2 The lithium nickel cobalt manganese composite oxide particles (first particles) represented by the average particle size D 2 is 5μm, LiNi 0.8 Co 0.1 Mn 0.1 O 2 Lithium nickel cobalt manganese composite oxide particles (second particles) represented by LiCoO 2 The particle size of the first particles was within a range of 8 μm or more and 12 μm or less. The particle size of the second particles was within a range of 2 μm or more and 6 μm or less. The particle size of the lithium cobalt composite oxide particles was within a range of 3 μm or more and 13 μm or less.
[0168] A slurry was prepared by suspending 93% by weight of a positive electrode active material consisting of 72% by weight of first particles, 8% by weight of second particles, and 20% by weight of lithium-cobalt composite oxide particles, 3% by weight of acetylene black and 2% by weight of graphite as a conductive agent, and 2% by weight of polyvinylidene fluoride (PVdF) as a binder in N-methylpyrrolidone (NMP) to a solids ratio of 82.3% by weight.
[0169] A battery was fabricated in the same manner as in Example 1, except that the positive electrode slurry was applied to both sides of the positive electrode current collector so that the thickness of the positive electrode mixture layer became 105 μm. Comparative Example 3
[0170] As a positive electrode active material, the average particle size D 1 is 25μm, LiNi 0.8 Co 0.1 Mn 0.1 O 2 The lithium nickel cobalt manganese composite oxide particles (first particles) represented by the average particle size D 2 is 5μm, LiNi 0.8 Co 0.1 Mn 0.1 O 2Lithium nickel cobalt manganese composite oxide particles (second particles) represented by LiCoO 2 The lithium cobalt composite oxide particles represented by the formula (1) were prepared. The particle size of the first particles was within the range of 8 μm or more and 25 μm or less. The particle size of the second particles was within the range of 2 μm or more and 6 μm or less. The particle size of the lithium cobalt composite oxide particles was within the range of 3 μm or more and 13 μm or less.
[0171] A slurry was prepared by suspending 93% by weight of a positive electrode active material consisting of 69% by weight of first particles, 11% by weight of second particles, and 20% by weight of lithium-cobalt composite oxide particles, 3% by weight of acetylene black and 2% by weight of graphite as a conductive agent, and 2% by weight of polyvinylidene fluoride (PVdF) as a binder in N-methylpyrrolidone (NMP) to a solids ratio of 75.5% by weight.
[0172] A battery was fabricated in the same manner as in Example 1, except that the positive electrode slurry was applied to both sides of the positive electrode current collector so that the thickness of the positive electrode mixture layer was 90 μm.
[0173] For the obtained battery, the abundance ratio (%) of the first particles expressed by the formula (1), the thickness T (μm) of the positive electrode mixture layer, and the 2D 1 / T value, 2D 1 / T×1.05, A3 / A1, T / 2(μm), T1S(μm 2 ), T2S(μm 2 ) was measured by the method described above. 2 ) and T2S(μm 2 ) was used to calculate T2S / T1S. T2S / T1S was calculated based on the abundance ratio (%), the thickness of the positive electrode mixture layer T (μm), and 2D 1 / T, 2D 1 / T×1.05, A3 / A1, and T / 2 (μm) are shown in Tables 1 and 2 below. [Measurement of discharge capacity 1] The battery thus produced was charged at a constant current of 1 C to 2.7 V in a 25° C. environment, then charged at a constant voltage until the current value reached 0.1 C, and after a 30-minute pause, discharged at a constant current of 0.5 C until the voltage reached 1.5 V. The discharge capacity at this time was taken as 1. [Cycle test] The battery for which discharge capacity 1 was measured was charged at a constant current of 2C to 2.7V in a 45°C environment, then charged at a constant voltage until the current value reached 0.1C, rested for 10 minutes, and then discharged at a constant current of 2C until the voltage reached 1.5V, and rested for 10 minutes. This cycle of charge, rest, discharge, and rest was counted as one cycle, and the cycle was repeated 1000 times. [Discharge capacity 2 measurement, discharge capacity rate] After the cycle test, the battery was cooled in a 25°C environment for 3 hours, and then charged at a constant current of 1C to 2.7V in a 25°C environment, and then charged at a constant voltage until the current value reached 0.1C. After a 30-minute break, the battery was discharged at a constant current of 0.5C until the voltage reached 1.5V. This was taken as discharge capacity 2. The discharge capacity rate was calculated as discharge capacity rate [%] = [discharge capacity 2] / [discharge capacity 1] x 100. [Measurement of capacity per unit volume of positive electrode] One side of the positive electrode prepared by the above procedure was peeled off with NMP, cut into 2 cm x 2 cm, and the thickness and weight of the positive electrode were measured. Separately, both sides of the positive electrode were peeled off with NMP, cut into 2 cm x 2 cm, and the thickness and weight of the current collector foil were measured. From these results, the weight of the active material in the sample and the density of the active material layer of the sample were obtained. The sample was dried at 95°C and -100 kPa for 12 hours. The dried sample was mixed with metallic lithium as the counter electrode and reference electrode, glass filter paper as the separator, and ethylene carbonate (EC) and diethyl carbonate (DEC) as the electrolyte in a volume ratio of 1:2 to form a non-aqueous solvent, and lithium hexafluorophosphate LiPF 6 A three-electrode glass cell was prepared using a solution prepared by dissolving the above in a solution at a concentration of 1.0 mol / L.
[0174] The glass cell was then placed at 25°C and in a potential range of 3.0-4.25V (vs. Li / Li +The initial charge / discharge test was performed at a current of 0.2 C. The battery was charged at a constant current up to 4.25 V, and constant voltage charging was continued for 10 hours, after which a 10-minute break was taken, and the battery was discharged at a constant current of 0.2 C down to 3.0 V.
[0175] The discharge capacity thus obtained was divided by the weight of the active material, and then further divided by the electrode density to obtain the capacity per unit volume of the positive electrode. The capacity per unit volume of the positive electrode in Example 1 was set to 1, and the values of the other examples are shown below.
[0176] [Table 1]
[0177] [Table 2]
[0178] In Examples 1 to 11, high capacity and good charge / discharge cycle characteristics were obtained. Since the large particles and small particles are present at a moderate ratio, a high capacity electrode with high packing density is obtained. Furthermore, since a large number of large particles with a small specific surface area are present on the current collector foil side exposed to a large current, the surface area of the active material present on the current collector foil side is small, side reactions with the electrolyte are suppressed, and when gas is generated, gas escape from the mixture layer is good, and the mixture layer is suppressed from slipping off. In Examples 1 to 11, T2S / T1S is greater than 2, satisfying the formula T2S>2×T1S (3). Therefore, the conductive agent is distributed in large amounts on the second surface (S2) side, which has a large electron conduction distance from the current collector foil, suppressing the current density distribution, and the discharge capacity rate after cycling is high.
[0179] LiNi 0.5 Co 0.2 Mn 0.3 O 2 Example 6, in which LiMn was used as the positive electrode active material 2 O 4In Example 7 using [lithium-containing metal oxide] as the positive electrode active material, both the capacity per unit and the discharge capacity retention rate were high. Therefore, when using a lithium-containing metal oxide as the positive electrode active material, a battery with high capacity and excellent charge-discharge cycle performance can be provided. In particular, the discharge capacity retention rate of Example 6 was as high as 93%, and LiNi 0.8 Co 0.1 Mn 0.1 O 2 used as the positive electrode active material was the same as the discharge capacity retention rate of Example 1. Therefore, by using a lithium-containing nickel manganese composite oxide represented by the general formula Li x Co 1-y-z Mn y Ni z O 2 (0 < x ≤ 1, 0 < y ≤ 1, 0 < z ≤ 1, 0 ≤ 1 - y - z ≤ 1) as the positive electrode active material, a battery with particularly excellent charge-discharge cycle performance can be provided.
[0180] In Example 8 with an aspect ratio of 1 and Example 9 with an aspect ratio of 1.8, both the capacity per unit and the discharge capacity retention rate were excellent. Therefore, when the aspect ratio of the electrode group is in the range of 1 or more and 1.8 or less, a battery with high capacity and excellent charge-discharge cycle performance can be provided.
[0181] In Example 10 using a separator with an air permeability of 20 sec / 100 ml and Example 11 using a separator with an air permeability of 100 sec / 100 ml, both the capacity per unit and the discharge capacity retention rate were excellent. Therefore, when the air permeability of the separator is 20 sec / 100 ml or more and 100 sec / 100 ml or less, a battery with high capacity and excellent charge-discharge cycle performance can be provided.
[0182] In Comparative Example 1, since the particle diameters of the active materials present in the electrode binder layer were uniform, the packing density was low, and the capacity per unit volume was low. Furthermore, since the proportion of small particles was high, the surface area of the active material was large, the side reaction with the electrolyte was large, the gas generation amount increased, the gas permeability from the binder layer was poor, and as a result, the binder layer slipped during the charge-discharge cycle, resulting in a low discharge capacity rate after the cycle. In Comparative Example 2, the particle diameter of the active material present in the electrode mixture layer was uniform, so that the packing density was low and the capacity per unit volume was low. In Comparative Example 3, the proportion of large particles unevenly distributed in the electrode mixture layer on the current collecting foil side was low, and therefore the surface area of the active material present on the current collecting foil side was large, causing a large side reaction with the electrolyte, and poor gas escape from the mixture layer, resulting in the mixture layer sliding off during charge / discharge cycles.
[0183] The active material contained in the electrode according to at least one of the above-described embodiments and examples comprises first particles of a lithium-containing metal oxide and an average particle diameter D 1 Average particle size D smaller than 2 and second particles of a lithium-containing metal oxide having the above structure. The first particles are present in a greater amount than the second particles. The first particles are unevenly distributed in the electrode. With such an electrode, a battery having a high capacity and excellent charge / discharge cycle performance can be realized.
[0184] Although some embodiments of the present invention have been described, these embodiments are presented as examples and are not intended to limit the scope of the invention. These novel embodiments can be implemented in various other forms, and various omissions, substitutions, and modifications can be made without departing from the spirit of the invention. These embodiments and their modifications are included in the scope of the invention and its equivalents described in the claims, as well as in the scope and spirit of the invention. The invention as originally claimed in the present application is set forth below. [1] An electrode comprising a current collector and a mixture layer containing an active material formed on at least one surface of the current collector, The active material comprises first particles of a lithium-containing metal oxide and an average particle size D 1 Average particle size D smaller than 2 and second particles of a lithium-containing metal oxide having the existence ratio of the first particles and the second particles represented by the following formula (1) is 60% or more and 90% or less, {A1 / (A1+A2)}×100 (1) When a distance from a first surface of the mixture layer that is in contact with the current collector to a second surface that is not in contact with the current collector is defined as T, A1 is the total area of the first particles on a surface of the mixture layer having a length of the distance T, and A2 is the total area of the second particles on the surface of the mixture layer, Distance 2D from the first surface to the second surface 1 / T, the first particles are unevenly distributed in a range of (A3 / A1)≧2D 1 / T×1.05 (2) Here, A3 is the total area of the first particles present in the area of the surface of the mixture layer, electrode. [2] The electrode according to [1], wherein the particle size of the first particles is in the range of 8 μm or more and 25 μm or less, and the particle size of the second particles is in the range of 0.5 μm or more and 7 μm or less and is smaller than the particle size of the first particles. [3] The electrode according to [1], wherein the particle size of the first particles is in the range of 8 μm or more and 25 μm or less, and the particle size of the second particles is in the range of 1 μm or more and 6 μm or less and is smaller than the particle size of the first particles. [4] The mixture layer further contains a conductive agent in the form of secondary particles, and the total area of the conductive agent included in the range from the first surface toward the second surface on the surface of the mixture layer to a distance T / 2 is defined as T1S (μm 2 ), and the total area of the conductive material included in the range from the second surface toward the first surface to a distance T / 2 is defined as T2S (μm 2 ) satisfies the following formula (3), T2S>2×T1S (3) The electrode according to any one of [1] to [3]. [5] The lithium-containing metal oxide is at least one selected from the group consisting of a lithium-containing nickel cobalt manganese composite oxide, a lithium-containing nickel manganese composite oxide, and a lithium-containing manganese composite oxide, and the electrode according to any one of [1] to [4]. [6] The lithium-containing metal oxide is Li a Ni (1-x-y) Co x Mn y O 2 (0.9 ≦ a ≦ 1.2, 0 < x ≦ 0.5, 0 < y ≦ 0.5, x ≧ y, 0.6 ≦ 1 - x - y ≦ 0.9), Li x Co 1-y-z Mn y Ni z O 2 (0 < x ≦ 1, 0 < y ≦ 1, 0 < z ≦ 1, 0 ≦ 1 - y - z ≦ 1), and Li x Mn 2 O 4 (0 < x ≦ 1), and is at least one selected from the group consisting of, and the electrode according to any one of [1] to [4]. [7] The active material further includes particles of a lithium-containing cobalt composite oxide, and the electrode according to any one of [5] or [6]. [8] A positive electrode composed of the electrode according to any one of [1] to [7], A negative electrode And a battery. [9] The battery according to [8], further including a separator having an air permeability of 20 sec / 100 ml or more and 100 sec / 100 ml or less.
[10] The battery according to [9], comprising an electrode group in which the positive electrode, the negative electrode, and the separator disposed between the positive electrode and the negative electrode are wound, and the aspect ratio of the electrode group is 1 or more and 1.8 or less.
[11] A battery pack including the battery according to any one of [8] to
[10] . [Explanation of symbols]
[0185] DESCRIPTION OF SYMBOLS 1...electrode group, 2...negative electrode, 2a...negative electrode current collector, 2b...negative electrode active material-containing layer, 3...positive electrode, 3a...positive electrode current collector, 3b...positive electrode active material-containing layer, 3c...positive electrode current collecting tab, 4...separator, 5...negative electrode terminal, 6...positive electrode terminal, 7...exterior member, 15...negative electrode terminal, 15a...negative electrode lead, 16...positive electrode terminal, 16a...positive electrode lead, 17a...metal container, 17b...sealing plate, 17c...insulating member, 20...battery pack, 23...assembled battery, 24...printed wiring board, 25...thermistor, 26...protective circuit, 27...current-carrying terminal, 28...positive electrode lead, 30...negative electrode lead, 36...protective sheet, 37...container, 38...lid.
Claims
1. An electrode including a current collector and a mixture layer formed on at least one surface of the current collector and including an active material, The active material includes first particles of a lithium-containing metal oxide and an average particle diameter D 1 Average particle size D smaller than 2 and second particles of a lithium-containing metal oxide having an existence ratio of the first particles and the second particles represented by the following formula (1) is 60% or more and 90% or less, {A1 / (A1+A2)}×100 (1) When a distance from a first surface of the mixture layer that is in contact with the current collector to a second surface that is not in contact with the current collector is defined as T, A1 is a total area of the first particles on a surface of the mixture layer having a length of the distance T, and A2 is a total area of the second particles on the surface of the mixture layer, A distance 2D from the first surface toward the second surface 1 / T, the first particles are unevenly distributed in a range satisfying the following formula (2): (A3 / A1)≧2D 1 / T × 1.05 (2) Here, A3 is the total area of the first particles present in the range on the surface of the mixture layer, An electrode, wherein the particle size of the first particles is within the range of 8 μm or more and 25 μm or less, the average particle size being the average particle size D 1 , and the particle size of the second particles is within the range of 1 μm or more and 6 μm or less and is smaller than the particle size of the first particles, the average particle size being the average particle size D 2 .
2. The mixture layer further contains a conductive agent in the form of secondary particles, and the total area of the conductive agent included in the range from the first surface toward the second surface to a distance T / 2 on the surface of the mixture layer is defined as T1S (μm 2 , the total area of the conductive agent included in the range from the second surface toward the first surface to a distance T / 2 is defined as T2S (μm 2 ) satisfies the following formula (3): T2S>2×T1S (3) 2. The electrode of claim 1.
3. The electrode according to any one of claims 1 to 2, wherein the lithium-containing metal oxide is at least one selected from the group consisting of a lithium-containing nickel-cobalt-manganese composite oxide, a lithium-containing nickel-manganese composite oxide, and a lithium-containing manganese composite oxide.
4. The lithium-containing metal oxide is Li a Ni (1-x-y) Co x Mn y O 2 (0.9≦a≦1.2, 0<x≦0.5, 0<y≦0.5, x≧y, 0.6≦1-xy≦0.9), Li x Co 1-y-z Mn y Ni z O 2 (0<x≦1, 0<y≦1, 0<z≦1, 0≦1-y-z≦1), and Li x Mn 2 O 4 The electrode according to any one of claims 1 to 2, which is at least one selected from the group consisting of (0<x≦1).
5. 5. The electrode according to claim 3, wherein the active material further comprises particles of a lithium-containing cobalt composite oxide.
6. An electrode described in any one of claims 1 to 2, wherein the lithium-containing metal oxide of the first particles and the lithium-containing metal oxide of the second particles are each a lithium-containing nickel-cobalt-manganese composite oxide.
7. A positive electrode comprising the electrode according to any one of claims 1 to 6; Negative electrode and Including batteries.
8. The battery according to claim 7 , further comprising a separator having an air permeability of 20 sec / 100 ml to 100 sec / 100 ml.
9. 9. The battery according to claim 8, comprising an electrode group in which the positive electrode, the negative electrode, and the separator disposed between the positive electrode and the negative electrode are wound, and the electrode group has an aspect ratio of 1 or more and 1.8 or less.
10. A battery pack comprising the battery according to any one of claims 7 to 9.
Citation Information
Patent Citations
Preparation method of power type lithium ion battery
CN111276757A
Positive electrode plate for secondary battery and manufacture thereof
JP2000011995A
Electrode for secondary battery, and secondary battery using this
JP2007157694A
Positive electrode plate, lithium-ion secondary battery, vehicle, and battery loading device
JP2009026599A
Positive-electrode active material for lithium secondary battery and its manufacturing method, and positive electrode for lithium secondary battery active material and lithium secondary battery using positive electrode
JP2009117241A
